2017
DOI: 10.1016/j.neuron.2017.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplastin and Basigin Are Essential Auxiliary Subunits of Plasma Membrane Ca2+-ATPases and Key Regulators of Ca2+ Clearance

Abstract: Plasma membrane Ca-ATPases (PMCAs), a family of P-type ATPases, extrude Ca ions from the cytosol to the extracellular space and are considered to be key regulators of Ca signaling. Here we show by functional proteomics that native PMCAs are heteromeric complexes that are assembled from two pore-forming PMCA1-4 subunits and two of the single-span membrane proteins, either neuroplastin or basigin. Contribution of the two Ig domain-containing proteins varies among different types of cells and along postnatal deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(120 citation statements)
references
References 57 publications
2
91
1
Order By: Relevance
“…Consistent with this proposition, it has been reported recently that TRAF6 efficiently binds to and regulates the stability of PSD-95 as a necessary step for the plasticity of hippocampal mature spines (Ma et al, 2017). Alternatively, neuroplastin could also change its predilection for interaction partners in young neurons as it becomes an essential subunit for the four paralogs in mature neurons (Bhattacharya et al, 2017;Herrera-Molina et al, 2017;Korthals et al, 2017;Schmidt et al, 2017;Gong et al, 2018).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Consistent with this proposition, it has been reported recently that TRAF6 efficiently binds to and regulates the stability of PSD-95 as a necessary step for the plasticity of hippocampal mature spines (Ma et al, 2017). Alternatively, neuroplastin could also change its predilection for interaction partners in young neurons as it becomes an essential subunit for the four paralogs in mature neurons (Bhattacharya et al, 2017;Herrera-Molina et al, 2017;Korthals et al, 2017;Schmidt et al, 2017;Gong et al, 2018).…”
Section: Discussionmentioning
confidence: 53%
“…Very recently, it has been discovered that neuroplastin interacts with all four plasma membrane Ca 2+ ATPases (PMCA1-4) stabilizing the surface expression of these pumps (Bhattacharya et al, 2017;Herrera-Molina et al, 2017;Korthals et al, 2017;Schmidt et al, 2017;Gong et al, 2018). Thus, we addressed the obvious question whether TRAF6 or neuroplastin require PMCA to promote dendritic protrusion density.…”
Section: Traf6 Confers the Spinogenetic Capacity To Neuroplastinmentioning
confidence: 99%
“…Recent investigations have revealed the extracellular immunoglobulin superfamily members neuroplastin (NPTN) and close paralog basigin (BASI) as key regulators of PMCA complexes. Supporting this, double knockout studies of NPTN and BASI demonstrated decreased Ca 2+ clearance 1 . In a paper by Gong et al published in Nature Communications in September 2018, a new structure of human PMCA1d (hPMCA1) in complex with the recently identified regulator neuroplastin is presented 2 .…”
mentioning
confidence: 70%
“…More recently, Schmidt et al . identified Nptn as a novel subunit of native plasma membrane Ca 2+ ‐ATPases (PMCAs ) . In addition, Korthals et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that several polymorphisms in the Nptn gene are correlated with schizophrenia, cortical thickness, and intellectual abilities in adolescents [9,10]. More recently, Schmidt et al [11] identified Nptn as a novel subunit of native plasma membrane Ca 2+ -ATPases (PMCAs). In addition, Korthals et al [12] reported that PMCA levels were dramatically reduced and Ca 2+ levels were significantly increased in internal stores of Nptn À/À T cells.…”
Section: Introductionmentioning
confidence: 99%